Melatonin Protects Mitochondrial Function and Inhibits Oxidative Damage against the Decline of Human Oocytes Development Caused by Prolonged Cryopreservation - Qi Zhu; Ding Ding; Han Yang; Weiwei Zou; Dandan Yang; Kaijuan Wang; Chao Zhang; Beili Chen; Dongmei Ji; Yan Hao; Rufeng Xue; Yuping Xu; et al. (Cells, 2022)
Melatonin (MT) can improve the effect of cryopreservation on oocytes by suppressing oxidative stress and maintaining the permeability of the oolemma. In this study, MT was firstly applied to human oocytes’ cryopreservation to explore the effect of prolonged cryopreservation on developmental competence and its role. Collected in vitro-matured human oocytes were cryopreserved in MT-containing or MT-free medium for 0 and 6 months; after warming, viable oocytes were assessed for developmental viability, intracellular protein expression, mitochondrial function, and oxidation-antioxidant system. Meanwhile, fresh oocytes were set as the control. The results showed that with the extension of cryopreservation time, the developmental competence of oocytes gradually declined, accompanied by the down-regulation of most mitochondrial function-related proteins, the reduction in ATP and GSH production, the increase in ROS accumulation, and the aggravation of the imbalance of ROS/GSH in oocytes. However, the participation of MT seemed to effectively mitigate these negative effects. Therefore, we speculate that melatonin may maintain normal ATP production and ROS/GSH balance in cryopreserved oocytes by protecting mitochondrial function and inhibiting oxidative damage, thereby effectively maintaining the developmental competence of human oocytes in prolonged cryopreservation.